DAMPAK KEBERADAAN HYPERMARKET TERHADAP PERUBAHAN GUNA LAHAN SEKITARNYA DI SURAKARTA - Fitriasti, Devi Nurul; Soedwiwahjono, Soedwiwahjono; Putri, Rufia Andisetyana (ARSITEKTURA, 2015)
Urban population growth in Indonesia to encourage increased economic activity. Surakarta city including influential city in Central Java and has developed quite rapidly. Sectors of the economy are on the rise Surakarta supported by means of existing trade. One means of trading in Surakarta namely hypermarkets, therefore hypermarket can be called as one of the vital means that the motor driving the economy of Surakarta. Hypermarkets need space to carry out trading activities and the development of hypermarkets in Surakarta mushroomed to exceed the limits of the city administration. Hypermarkets have some impact on the surrounding environment, among others, changes in land use. Problems in this research is to know how big the impact of the presence of urban hypermarket Surakarta to changes in land use in the vicinity. Land use changes that occur are changes in land use and changes in the intensity of land. The method used in this study is based on quantitative research paradigms of positivism. For the method of data collection in this study done by the secondary survey to the relevant agencies and the primary survey in the form of observations and interviews related to changes in land use in the surrounding urban hypermarket Surakarta. The results of this study is the first to change the land use of non-commercial land into commercial land is happening around urban hypermarket Surakarta impact of 56.76%. Both the change in land iintensitas of non-commercial land into commercial land is happening around urban hypermarket impact Surakarta 27.25%. It was found that the impact of Surakarta urban hypermarkets are to changes in the surrounding land. Keywords: hypermarket, land use, commercial